The Symbolic Meaning of Bugis Traditional Wedding Clothes in Soni Village: A Semiotic Study of Charles Sanders Peirce's Theory - Riska Hermawati; Juniati Juniati; Andi Bismawati; Yunidar Yunidar; Hasnur Ruslan (Global Education Journal, 2026)
In various traditions in Indonesia, traditional clothing has an important position because it is used in sacred ceremonies, including wedding ceremonies. This research aims to describe the shape and meaning of symbols contained in Bugis traditional wedding clothes. The research uses a qualitative method with a descriptive approach. Data was obtained through observation, interviews, and documentation with informants consisting of traditional elders and the Bugis community who understood the meaning of traditional bridal attire. Data is analyzed through the stages of data reduction, data presentation, and conclusion drawn. The results of the study show that the symbols on Bugis traditional wedding clothes are divided into verbal symbols and nonverbal symbols. Verbal symbols are obtained from the informant's explanation of the meaning of colors, jewelry, and traditional clothing related to purity, fertility, glory, social status, loyalty, responsibility, and siri' values in the life of the Bugis people. Nonverbal symbols appear in elements of clothing and accessories, such as wedding dresses, lipa' sabbe, potto, ponto, necklaces, giwang, crowns, keris, and songko, each of which contains philosophical meanings about honor, courage, welfare, fertility, happiness, and the hope of a harmonious domestic life. The findings of the study show that Bugis traditional wedding clothes not only function as wedding clothes, but also as a representation of cultural values, social identity, and ancestral heritage that are full of symbolic meaning.